Radical Solar Energy Startups in Kenya and Tanzania - Joni Karjalainen; Juho Ruotsalainen; Sirkka Heinonen; Rob Byrne (University of Turku: Finland Futures Research Centre, 2022)
This working paper focuses on radical startups of solar photovoltaics (PV) in Kenya and Tanzania. The research was conducted in the Neo-Carbon Energy project (2014-2017) and finalized in the science-communication project Great Electrification in Peer-to-Peer Society (2018), conducted at the Finland Futures Research Centre (FFRC) in the University of Turku.
The purpose of the working paper is to test one of the Neo-Carbon Energy project’s transformative scenarios, called Radical Startups 2050, and reflect it in Kenya and Tanzania. In East Africa, over 80 million people could benefit from mobile-enabled energy services. Kenya and Tanzania are pioneering solar energy markets in sub-Saharan Africa, where policy makers are seeking to achieve ‘sustainable energy for all’ objectives, and are increasingly focussed on entrepreneurial clean energy technology ventures. Many solar companies have started their operations in these markets, which has strengthened a narrative of a market-led energy transition in East Africa. Remarkably, there has been limited analysis about the factors that have enabled these pioneering ventures to emerge.
The scenario testing is performed by first examining the historic evolution of the solar PV niche in Kenya and Tanzania, which shows how multiple pioneers built a solar energy niche over a few decades before the current solar innovation boom. The situation at the present shows how a growing number of ‘heroic’ solar entrepreneurs from home and abroad are now addressing energy poverty in East Africa. The company case studies describe their business models, proposed solutions and corporate histories to explore how they have emerged, and tell a story of ‘radical’ startups now pioneering in different ways. This exercise opens up novel avenues to think critically about the role of innovation in development. At least six important considerations seem to deserve further attention.
The working paper opens up novel debates and questions related to this strategy, and provokes thoughts on the everyday practices that are promised to make innovation to deliver on environmental, social and economic goals. Of particular future policy relevance is the issue of learning and value retention from innovation activities.